Detection of mycobacterium tuberculosis dna in buccal swab samples from children in lima, Peru - Juan A., Flores (2020)
We examined Mycobacterium tuberculosis DNA detection from buccal swab samples collected from children in Lima, Peru. DNA was extracted and amplified via real-time polymerase chain reaction. Sensitivity was 21% (95% confidence interval [CI]: 7%–42%) in 24 culture-confirmed tuberculosis cases and 4.6% (95% CI: 1%–13%) in 65 clinically diagnosed unconfirmed cases. Sensitivity was highest for smear-positive tuberculosis. Specificity was 99% in the 199 controls (95% CI: 96%–100%).